Lipoprotein(a) and Oxidized Phospholipids in Calcific Aortic Valve Stenosis - Yeang, Calvin (Curr Opin Cardiol, 2016)
PURPOSE OF REVIEW: Calcific aortic valve stenosis (AS) affects over 1 million patients in the US. Effective medical therapies do not exist. With the aging of the population and increase in incidence of AS, improved understanding of this disease and novel therapies to reduce the progression of AS and need for aortic valve replacement (AVR) are urgently needed. RECENT FINDINGS: Lipoprotein(a) [Lp(a)] is the only monogenetic risk factor for AV calcification and AS. Elevated Lp(a) levels are a strong, causal, independent risk factor for AS, as demonstrated in epidemiological, genome-wide association studies and Mendelian randomization studies. Lp(a) is the major lipoprotein carrier of oxidized phospholipids (OxPL) which are pro-inflammatory and promote calcification of vascular cells, two key pathophysiological drivers of AS. Moreover, Lp(a)-associated enzymes and lipids derived from breakdown of OxPL have been implicated in the pathogenesis of AS. These mechanistic insights likely explain the recent findings that elevated plasma Lp(a) and OxPL on apoB containing lipoproteins (OxPL-apoB) predict progression of pre-existing AS and need for AVR. The failure of the statin trials in AS may be partially explained by the fact that statins, as monotherapy or in combination with ezetimibe, have neutral or Lpa(a) raising effects, as has been shown most recently in the ASTRONOMER trial. Antisense oligonucleotides targeted to apo(a) are in Phase 2 clinical development and shown to lower both Lp(a) and OxPL-apoB. SUMMARY: Lp(a) and OxPL are key therapeutic targets in AS. Strategies aimed at potent Lp(a) lowering to normalize levels and/or suppress the pro-inflammatory effects of OxPL may be beneficial for preventing progression of AS and need for AVR.